Pendampingan Pembuatan Kripik Pala Balado - Irma Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2023)
Nutmeg is one of the natural resources in the form of spices which are often found in North Maluku Province, especially the city of Ternate. In general, the parts of the nutmeg that have been used so far are the seeds and the mace. Meanwhile, the nutmeg flesh has only been considered as waste. However, in line with the times, nutmeg flesh has begun to be used by processing it into food or drinks in the form of syrup. One form of processed nutmeg made in this training is balado nutmeg chips. Training activities for making balado nutmeg chips are carried out with the aim that Gatra Buana Guarabati Tidore Academy students who are not included in the creative gatra group can learn to make waste nutmeg flesh into products that can be consumed and have economic value. The venue for the training on making balado nutmeg chips at the Gatra Buana Academy, Gurabati Tidore. The stages in this activity include; (1) pre-activity, which includes licensing and site preparation activities; (2) implementation of actions, which include socialization activities and assistance in making balado nutmeg chips. The results of this activity showed that 68 students from the Gurabati Tidore Midwifery Academy who participated in this activity showed their creativity and high enthusiasm in producing a product in the form of balado nutmeg chips.